Intercarpal Ligament Injuries Associated With Distal Radius Fractures. Issue 20 (15th October 2019) - Fowler, Timothy P.
Abstract : Injuries to the scapholunate (SL) and lunotriquetral (LT) interosseous ligaments occur in approximately one third of distal radius fractures. The diagnosis of these injuries is challenging because plain radiographs are not reliably diagnostic. Wrist arthroscopy may be the most accurate way to examine and diagnose soft-tissue injuries of the carpus adjacent to a distal radius fracture. Treatment options for SL and LT ligament injuries include open repair and/or percutaneous pinning. Because the natural history of these injuries is unclear, the necessity of diagnosing and treating these SL and LT interosseous ligament defects remains speculative.